2011
DOI: 10.2215/cjn.02340310
|View full text |Cite
|
Sign up to set email alerts
|

The Associations of Social Support and Other Psychosocial Factors with Mortality and Quality of Life in the Dialysis Outcomes and Practice Patterns Study

Abstract: SummaryBackground and objectives This study aimed to investigate the influence of social support and other psychosocial factors on mortality, adherence to medical care recommendations, and physical quality of life among hemodialysis patients.Design, setting, participants, & measurements Data on 32,332 hemodialysis patients enrolled in the Dialysis Outcomes and Practice Patterns Study (1996 to 2008) in 12 countries were analyzed. Social support and other psychosocial factors related to ESRD and its treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
111
1
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(131 citation statements)
references
References 29 publications
7
111
1
12
Order By: Relevance
“…That may indicate that patients including their family members, caregivers and even the social employers should also be educated about treatment choices and therapeutic goals for kidney failure [6,26]. What's more, social support programs such as spiritual care, employment counseling or vocational rehabilitation may lower some of the barriers to employment and can help individuals with the greatest potential for workforce participation [27][28][29][30]. We acknowledge some potential limitations in our study.…”
Section: Discussionmentioning
confidence: 99%
“…That may indicate that patients including their family members, caregivers and even the social employers should also be educated about treatment choices and therapeutic goals for kidney failure [6,26]. What's more, social support programs such as spiritual care, employment counseling or vocational rehabilitation may lower some of the barriers to employment and can help individuals with the greatest potential for workforce participation [27][28][29][30]. We acknowledge some potential limitations in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the items discussed in this review, comorbidity burden and social status may be of added value when focusing on risk assessment, because both are associated with mortality. However, for social status, this was assessed in the prevalent population only (53). A GA focusing on rehabilitation may additionally include geriatric syndromes, such as delirium, incontinence, constipation, osteoporosis, and sensory deficits, because these issues may be amenable to interventions that could potentially improve quality of life (52).…”
Section: Discussionmentioning
confidence: 99%
“…Babaei et al (24) in a study conducted on 719 patients with diabetes aimed at examining their awareness and understanding of the disease and its complications indicated that the patients had low levels of knowledge about diabetes and its complications and most of them needed training. A longitudinal study (25) analyzed data on 32,332 patients undergoing dialysis in 12 nations and concluded that low social support and other social and mental factors were significantly associated with a high risk of mortality. Since hemodialysis is one of the most discussed issues related to healthcare worldwide, including Iran (26), carrying out new research to examine the role of social support, illness perceptions, and resilience in managing this disease and reducing its complications is of significant importance.…”
Section: Introductionmentioning
confidence: 99%